Response surface methodology for optimization of lipase immobilization conditions on nanofibers grafted with polyglycidyl methachrylate (PGMA) - Alkhatib, Ma'an Fahmi Rashid; Bahrudin, Nik Adlin; Mohd. Salleh, Hamzah; Nasef, Mohamed Mahmoud (IMDD, 2017)
Immobilization of lipase enzyme originated from wheat germ on nylon -6- grafted with PGMA was studied. Face centered central composite design (FCCCD) under response surface methodology (RSM) was used to design the experiment in order to distinguish the optimum immobilization conditions for highest enzyme activity and to study the interactions between the various parameters. The polymer was activated with diethyl amine/ethanol to introduce amine functional group to facilitate covalent bonding with the enzyme. The immobilization conditions were 2-10 h for immobilization time; 6-8 for pH and 0.4-1.0 mg/ml for enzyme concentration. ANOVA revealed that optimum lipase activity of 0.287 U/ml was achieved at immobilization time of 5 h, pH of 6 and 1.0 mg/ml for enzyme concentration. Kinetics studies of both immobilized and free lipase were conducted to study the effect of immobilization on enzyme behavior. Amongst the tested models, Lineweaver-Burk Plot best fitted the data with Vmax and Km values of 0.024 mM/min and 10.321 mM for free lipase and 0.012 and 7.250 for immobilized lipase, respectively. The lower value of Km for immobilized lipase enzyme compared to free enzyme indicates a stronger and more efficient binding of substrate. Vmax on the other hand exemplify how quick the enzyme catalyzes the reaction. Lower Vmax for immobilized enzyme designates lower enzyme rate.